You're the problem, it's you : a novel - Alban, Emma R. (Alban, Emma R. Mischief & Matchmaking (Series), 2024)
Bobby Mason is sick of being second best: born the spare, never trusted with family responsibility, never expected to amount to much. He's hungry to contribute something that matters, while all around him his peers are squandering their political and financial power, coasting through life. Which is exactly why he can't stand the new Viscount Demeroven. James Demeroven is a disappointment to his stepfather, and Bobby keeps pointing out James's failures. But when their families are threatened, Bobby and James must find a way to work together.